KUPAS TUNTAS GANGGUAN MENSTRUASI DISMENORE PADA REMAJA - Ratnasari, Febi; Suprobowati, Dita Pratiwi; Tias , Eliska; Septian, Fauzy; Ramadhayanti, Ghita; Muhnandar, Ilfan Sarif; Rahayu, Kustini; Mentari, Mentari; Qamrul, Said; Ningsih, Siti Wahyu; Hartati, Sri; Nurpaidah, Tika; et al. (Nusantara Hasana Journal, 2022)
Adolescence is a period of maturation of the human reproductive organs and is often called puberty. In adolescent girls, puberty is marked by the presence of menarche or the first menstruation. The results of the research of the reproductive health information and counseling center (PIK-KRR) The incidence of dysmenorrhea consists of 72.89% primary dysmenorrhea, 27.11% secondary dysmenorrhea and the incidence is 45%-90% of productive women tormented by desminorrhea. Objective to increase knowledge about menstrual disorders in adolescents and the management of dysmenorrhea. Methods: Health Education with the target audience of young people. From the results of Health education, it was found that adolescents can recognize the factors that affect the menstrual cycle and know the treatment for dysmenorrhea.